The Mobile Lower Body Negative Pressure Gravity Suit for Long-Duration Spaceflight - Ashari, Neeki; Hargens, Alan R. (Frontiers in Physiology, 2020)
Spaceflight Associated Neuro-ocular Syndrome, bone decalcification, and muscle atrophy are among the most prevalent risks associated with long-duration spaceflight. Implementing the lower body negative pressure (LBNP) method is a potential countermeasure for these risks. LBNP counteracts head-ward fluid shifts and generates ground-reaction forces (GRFs). GRFs are beneficial for maintaining bones and muscles by producing gravity-like loads experienced on Earth. Currently, LBNP devices are large/bulky and usually require the subject to maintain a stationary position. However, our new mobile gravity suit is relatively small, untethered, and flexible in order to improve mobility in space. We hypothesized that this novel mobile gravity suit generates greater GRFs than a standard LBNP chamber. While lying supine, GRF data were recorded in both devices using foot sole sensors and a weight scale. At -40 mmHg, the gravity suit generated a mean maximum bodyweight of 125% 22% (P<0.02) whereas the standard LBNP chamber generated 91% 24%. The standard LBNP chamber generated a single force on the stationary subject, which was expressed as AW(LBNP) = GRF, where Aw = cross-sectional area (CSA) of waist seal. However, the mobile gravity suit generated an additional force based on the following equation, (AF + AW)LBNP = GRF, where AF = CSA of subject’s feet. The additional force was further expressed as F1 + F2 = AFLBNP, where F1 = spinal loading force, F2 = waist shear force, and AFLBNP = the total downward foot force. Thus, the mobile gravity suit produces higher percentages of bodyweight due to the suit's novel design.